Does Ontogenesis of Social Ontology Start with Pretence? - Gaetano Albergo (Rosenberg & Sellier, 2016)
Rakoczy and Tomasello follow Searle in claiming that rule games need status function assignment and constitutive rules. But, in the case of pretend play, it is not easy to put together these notions with the natural world knowledge necessary to engage in it. If we consider the pretended scenario as a possible world, metaphysically possible, then, how can we abandon the natural necessity implicit in it? The rules of pretend-inference can have a robustly objective status. On this view pretence stands to pretending as truth stands to belief.